Financial Incentives and Professionals’ Work Tasks: The Moderating Effects of Jurisdictional Dominance and Prominence - Chown, Jillian (Organization Science, 2020)
This research addresses the important question of how organizations can use financial incentives to influence the work tasks of their professional workforce—a constituency that is notoriously difficult to manage because of their specialized knowledge, considerable autonomy, strong socialization, and powerful professional norms. In particular, I explore how a baseline incentive effect is moderated by two features of professionals’ tasks and jurisdictions: jurisdictional dominance (i.e., how much the profession controls the provision of the task relative to other professions) and jurisdictional prominence (i.e., how commonly provided the task is within a profession relative to other tasks). Using data on thousands of physician tasks from Ontario, Canada, and a difference-in-differences empirical design, I find that professionals’ incentive responses are smaller when a profession has higher jurisdictional dominance over a task, but are larger when the task has higher jurisdictional prominence within the profession. This research contributes to the literature on professions and professionals in multiple ways. First, I introduce the concepts of jurisdictional dominance and jurisdictional prominence, distinguishing them from each other and from existing conceptions of professional control. Second, this study shows that financial incentives can be an effective tool for influencing professionals, but highlights that their efficacy is shaped by a task’s jurisdictional dominance and jurisdictional prominence. Finally, I show that these new conceptions of jurisdictional control influence professionals’ behaviors in meaningful ways and should therefore be considered in future studies of professions.